1983
DOI: 10.1523/jneurosci.03-12-02545.1983
|View full text |Cite
|
Sign up to set email alerts
|

The activity of neurons in the rostral medulla of the rat during withdrawal from noxious heat

Abstract: Neurons of the rostral ventromedial medulla (RVM) have been implicated in the modulation of nociceptive transmission. In order to further analyze their role in pain behavior, we studied their activity while eliciting the tail flick reflex with noxious heat. Recording sites were regions in the RVM from which microstimulation (less than or equal to 10 microA, 400 mu sec, 50 Hz continuous pulse trains) inhibited the tail flick reflex. Extracellular unit activity and tail temperature were recorded, stored, and plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
267
2
3

Year Published

1987
1987
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 454 publications
(280 citation statements)
references
References 36 publications
8
267
2
3
Order By: Relevance
“…The presence of numerous PAG neurons that do not show TF-related activity distinguishes this region from the RVM, where the majority of cells studied exhibited TF-related changes in activity (Fields et al, 1983a;Barbaro et al, 1986). Although a role for these neurons in pain modulation should not be ruled out, it is also possible that they are involved in one or more of the many functions that have been attributed to the PAG.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The presence of numerous PAG neurons that do not show TF-related activity distinguishes this region from the RVM, where the majority of cells studied exhibited TF-related changes in activity (Fields et al, 1983a;Barbaro et al, 1986). Although a role for these neurons in pain modulation should not be ruled out, it is also possible that they are involved in one or more of the many functions that have been attributed to the PAG.…”
Section: Discussionmentioning
confidence: 95%
“…In the RVM, 2 classes of cells have been identified that show changes in activity at the time of the tail-flick response (TF) elicited by noxious heat (Fields et al, 1983a). We now report that neurons in the PAG region also show changes in activity related to TF.…”
mentioning
confidence: 84%
See 3 more Smart Citations